2003
DOI: 10.4102/sajip.v29i4.125
|View full text |Cite
|
Sign up to set email alerts
|

Koherensiesin, selfdoeltreffendheid, lokus van beheer en uitbranding by maatskaplike werkers

Abstract: The objective of this article is to report on the relationships between social workers’ sense of coherence, self-efficacy and locus of control on the one hand and burnout on the other hand, and the extent to which these variables can predict their burnout. A survey design was used. The study population consisted of 107 social workers. Four questionnaires were used in the research, namely the Orientation to Life Questionnaire, the General Perceived Self-Efficacy Scale, the Work of Locus of Control Scale and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Another personality factor that contributes to burnout is low generalised self‐efficacy (Rothmann and Malan, 2002). Generalised self‐efficacy is a general, stable cognition (trait) that individuals have and carry with them, and which reflects the expectation that they possess the ability to perform tasks successfully in a variety of achievement situations (Rothmann, 2003).…”
Section: Background and Conceptual Clarificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another personality factor that contributes to burnout is low generalised self‐efficacy (Rothmann and Malan, 2002). Generalised self‐efficacy is a general, stable cognition (trait) that individuals have and carry with them, and which reflects the expectation that they possess the ability to perform tasks successfully in a variety of achievement situations (Rothmann, 2003).…”
Section: Background and Conceptual Clarificationmentioning
confidence: 99%
“…Generalised self‐efficacy is a general, stable cognition (trait) that individuals have and carry with them, and which reflects the expectation that they possess the ability to perform tasks successfully in a variety of achievement situations (Rothmann, 2003). According to Rothmann and Malan (2002) a significant relationship exists between generalised self‐efficacy and personal accomplishment, as well as between generalised self‐efficacy and cynicism.…”
Section: Background and Conceptual Clarificationmentioning
confidence: 99%
“…It seems reasonable to expect that a three-factor structure will be obtained in this study. Confirmatory factor analyses by Rothmann and Jansen van Vuuren (2002), Rothmann and Malan (2003), Kruger et al (2002) and Storm and Rothmann (2003a) consistently showed low loadings of item 13 on Cynicism. Despite various studies regarding the factor structure of the MBI-GS as described above, the equivalence of the factor structure for different language groups has not been studied to date.…”
mentioning
confidence: 92%
“…Rothmann and Malan (2003) found higher alphas (Exhaustion = 0,89; Cynicism = 0,76; Professional Efficacy = 0,85) while Kruger, Veldman, Rothmann and Jackson (2002) found lower alphas for Cynicism (0,72) and Professional Efficacy (0,69). Storm and Rothmann (2003a) found alpha coefficients of 0,88 (Exhaustion), 0,78 (Cynicism) and 0,79 (Professional Efficacy) in a sample of police officers in South Africa.…”
mentioning
confidence: 99%
“…A total of 79 publications were left: 45 Masters Dissertations, 10 Ph.D. Theses and 24 journal articles. A few of the Masters and Ph.D. studies were also published as journal articles (Coetzee, 1999;Coetzee & Rothmann, 1999;Kriel, 2004;Kriel, Wilders, & Strydom, 2008;Kriel, Wilders, Strydom, & Breytenbach, 2005Laubscher, 2001;Laubscher, Strydom, & Dreyer, 2003;Malan, 2001aMalan, , 2001bPretorius, 2000;Pretorius & Rothmann, 2001;Redelinghuys, 2003;Redelinghuys & Rothmann, 2005;Rothmann & Malan, 2003;Van Eeden, 1997;Van Eeden & Wissing, 2008). No books or book chapters published in Afrikaans could be found.…”
Section: The Search For Salutogenesis Literature In the Afrikaans Lanmentioning
confidence: 99%